Hubungan Status Sosial Ekonomi Orang Tua dengan Prestasi Belajar Al-Quran Santri TPQ Al-Huda Kota Banda Aceh - Raiyan, Raiyan; Widyanto, Anton; Hatta, Kusmawati (Desultanah: Journal Education and Social Science, 2023)
This study aims to determine the relationship between parents' economic status and the learning achievement of TPQ Al-Huda students in Banda Aceh City. This study uses quantitative methods that are correlational, looking at the relationship between variable X and variable Y. The instrument used for variable X is a questionnaire and the instrument for variable Y is a report card value. The research sample used was 20 respondents. The research data were analyzed statistically descriptively (frequency and average) and inferentially using the Product Moment correlation test (r-test). The results showed that the economic status of the parents of students was in the low category, the learning achievement of students was high /very good, and there was no relationship/correlation between the economic status of parents and the learning achievement of students, where the correlation efficiency in the category was very low. The implication of the research is that not always the economic status of parents is a determining factor for children's learning success and many other factors that can influence it